Spontaneous resolved cervical spine epidural hematoma: A case report - Fattahi, Arash (Surg Neurol Int, 2017)
BACKGROUND: Cervical spine epidural hematomas (CSEH) are rare, and surgical intervention is typically required. Here, we present the rare case of a CSEH resulting from chiropractic manipulation successfully treated conservatively. CASE DESCRIPTION: A 44-year-old female with cervical myelopathy presented with a mild quadriparesis following manipulation by a chiropractor. Although magnetic resonance (MR) documented a CSEH, the lesion was treated nonsurgically as the patient refused operative intervention. Four days later, the patient demonstrated spontaneous improvement. Furthermore, the 1-month post manipulation cervical MR showed resolution of the CSEH mass effect, and her myelopathy fully resolved. CONCLUSION: Few studies document the efficacy of conservative treatment of CSEH. In this case, a patient with cervical myelopathy presented with a mild quadriparesis following chiropractic manipulation. Although MR documented a CSEH, she refused surgery, but fortunately improved neurologically within the next 4 days and was intact within 1 postoperative month. We recommend performing more powerful studies with large sample size to better define criteria for conservative vs. surgical treatment of CSEH.